INFLUENCE OF PRODUCTION COSTS ON INCOME OF OIL PALM FARMERS (Elaeis Guineensis) - Susan Novrini; Surya Dharma; Annur Haposan Parlindungan (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2022)
Oil palm plantations were first introduced in Indonesia by the Dutch in 1848. Oil palm (Elais Guinensiss) is one of the plantation commodities that occupies an important position as a source of foreign exchange for Indonesia, so it has bright prospects. One of the oil palm producing areas in Labuhan Batu Regency is Bulu Cina Village. This study aims to (1) find out how the effect of production costs on the income of oil palm farmers, (2) to find out how much profit the oil palm farmers get. The method of determining the research area is purposive, the sampling method is by census (saturated sampling), data collection is primary data and secondary data, data analysis method is regression analysis, to answer the second problem using the income formula. The results showed (1) Based on the results of the regression there was a simultaneous significant effect of production costs on the income of oil palm farmers. (2) Based on the regression results, there is a partial significant effect of fertilization costs on the income of oil palm farmers, (3) Based on the regression results, there is a partial significant effect of FFB transportation costs on the income of oil palm farmers, (4) Based on the regression results there is a partial significant effect the cost of weed control on the income of oil palm farmers, (5) Based on the regression results, it can be seen that partially there is no significant effect on the cost of procurement of harvesting equipment on the income of oil palm farmers, (6) The average income of oil palm farmers received per year is Rp 69,239,566, - for an average land area of 1.9 hectares. The average production cost incurred by farmers per year for an average land area of 1.9 ha is Rp. 15,238,900,-.